Pipeline Logic and Culpability: Establishing a Continuum of Harm for Sacrifice Zones - Randolph, Ned (Frontiers in Environmental Science, 2021)
This article builds on the concept of Energy Sacrifice Zones, which has been used as a heuristic for areas negatively impacted by environmental degradation and/or pollution that harms nearby residents for broader economic gains elsewhere. Environmental justice scholars have since the 1980s identified urban “fence-line” communities as Sacrifice Zones, such as those along the industrialized Mississippi River corridor downstream of Baton Rouge, La., where public health and property values are impacted by plant emissions. More recent scholarship has identified analogous dispossession in coastal Louisiana, where indigenous and communities of color suffer environmental degradation and land loss from oil industry practices. Coastal oil and gas operations have left behind thousands of miles of pipelines, canals and subsiding oil fields that have accelerated marsh desiccation and land loss. This article argues that both inland and coastal areas of Louisiana are being sacrificed by the fossil fuel industry on a continuum of harm along pipelines from wellheads to inland plants. Oil wells, refineries, and petrochemical plants exist as nodes along a single line of production and manufactured demand for petroleum-based products, which also litter waterways and oceans. Such a continuum establishes a single Sacrifice Zone that conjoins multiple sites. Harmed communities need not be adjacent to one another to be considered logically contiguous and, therefore, subject to consideration of collective harm as long as they are linked by the material infrastructure that connects fossil fuel extraction, production and distribution. This zone of harm, once established, could be used to inform decision makers with more accurate and complex pictures of social and public health costs of industrial emissions and practices, particularly when considering proposals for plant expansions or new facilities. They may also be used to determine legal culpability in restitution claims by communities bearing the burden of the carbon economy.